Genotypic and Phenotypic Characterization of blaNDM–7-Harboring IncX3 Plasmid in a ST11 Klebsiella pneumoniae Isolated From a Pediatric Patient in China - Shao, Chunhong; Hao, Yingying; Wang, Yong; Jiang, Meijie; Jin, Yan (Frontiers in Microbiology, 2020)
NDM-7, a variant of New Delhi metallo-beta-lactamases (NDM), has the highest carbapenem-hydrolyzing activity. NDM-7-producing enterobacteria have been reported in many countries. In this study, we reported NDM-7 production in ST11 Klebsiella pneumoniae isolated from a boy hospitalized in the pediatric intensive care unit of a teaching hospital in China. The isolate exhibited resistance to β-lactam antimicrobials, quinolones, and trimethoprim/sulfamethoxazole, and it harbored blaNDM–7, blaCTX–M–15, qnrA, qnrB, and qnrS. The serotype of the isolated K. pneumoniae was assigned as K1, and it contained three virulence genes, including kfuBC, uge, and fim. The blaNDM–7 gene was located on a conjugative IncX3 plasmid designated as pB14NDM-7. This plasmid was fully sequenced and compared with the available blaNDM–7-harboring IncX3 plasmids. pB14NDM-7 contained a conserved genetic context of ISkox3-umuD-IS26-ΔTn125-IS5-ΔTn125-IS3000-ΔTn2. pB14NDM-7 showed 99% nucleotide identity and the same genetic context with three blaNDM–7-harboring IncX3 plasmids obtained from Escherichia coli in China. Our results indicate that IncX3 plasmid may contribute to the prevalence of blaNDM–7 in China. The high prevalence of NDM variants worldwide highlights the critical need for careful monitoring and control of the rapid dissemination of blaNDM.